Reaching task performance is associated to neuromuscular junction adaptations in rats with induced diabetes mellitus - Estrada-Bonilla,Y.C. (2020)
Upper limb performance is affected by diabetes mellitus (DM). Neuromuscular junction (NMJ) is a key structure to understand the relationship between performance and morphology in DM. The aim of the study was to analyze NMJ plasticity due to DM in an animal model and its relationship with the function of forelimbs in rats. Twelve Wistar rats were divided into control (C) and DM groups. Animals were trained to perform a grasping task, following procedures of habituation, shaping, and reaching task. DM was induced using streptozotocin. Forelimb neuromuscular performance for dexterity was evaluated one day before DM induction and five weeks following induction. After that, biceps, triceps, and finger flexors and extensors were removed. Connective tissue and muscle fiber cross-sectional area (CSA) were measured. NMJ was assessed by its morphometric characteristics (area, perimeter, and maximum diameter), using ImageJ software. Motor performance analyses were made using single pellet retrieval task performance test. Student’s t-test was used for comparisons between groups. A significant decrease in all NMJ morphometric parameters was observed in the DM group compared with the C group. Results showed that DM generated NMJ retraction in muscles involved in a reaching task. These alterations are related to signs of muscular atrophy and to poor reaching task performance. In conclusion, induced DM caused NMJ retraction and muscular atrophy in muscles involved in reaching task performance. Induced DM caused significantly lower motor performance, especially in the final moments of evaluation, when DM compromised the tropism of the muscular tissue.